Current status of ECMO for massive pulmonary embolism - Davies, Mark G.; Hart, Joseph P. (Frontiers in Cardiovascular Medicine, 2023)
Massive pulmonary embolism (MPE) carries significant 30-day mortality and is characterized by acute right ventricular failure, hypotension, and hypoxia, leading to cardiovascular collapse and cardiac arrest. Given the continued high mortality associated with MPE, there has been ongoing interest in utilizing extracorporeal membrane oxygenation (ECMO) to provide oxygenation support to improve hypoxia and offload the right ventricular (RV) pressure in the belief that rapid reduction of hypoxia and right ventricular (RV) pressure will improve outcomes. Two modalities can be employed: Veno-arterial-ECMO is a reliable process to decrease RV overload and improve RV function, thus allowing for hemodynamic stability and restoration of tissue oxygenation. Veno-venous ECMO can support oxygenation but is not designed to help circulation. Several societal guidelines now suggest using ECMO in MPE with interventional therapy. There are three strategies for ECMO utilization in pulmonary embolism: bridge to definitive interventional therapy, sole therapy, and recovery after interventional treatment. The use of ECMO in MPE has been associated with lower mortality in registry reviews, but there has been no significant difference in outcomes between patients treated with and without ECMO in meta-analyses. Considerable heterogeneity in studies is a significant weakness of the available literature. Applying ECMO is also associated with substantial multisystem morbidity due to a systemic inflammatory response, hemorrhagic stroke, renal dysfunction, and bleeding, which must be factored into the outcomes. The application of ECMO in MPE should be combined with an aggressive interventional pulmonary interventional program and should strictly adhere to the current selection criteria.